A Comprehensive Analysis of the Spectrophotometric and Medicinal Aspects of Ruthenium as its Coordination Compounds - Nisha; Arora, Tanu; Devi, Khushboo; Agnihotri, Nivedita (RSYN Proceedings, 2025)
Numerous scientific groups have been actively working on inorganic antitumor drugs for a long time and they have developed a number of metal complexes, particularly those involving ruthenium in different oxidation states. Due to their low systemic toxicity and selective antimetastatic effects against animal models, ruthenium complexes are currently a hot topic in medicinal chemistry. Ruthenium compounds seem to bind to DNA and enter tumour cells fairly well. Besides their antitumor activity, ruthenium complexes are also being evaluated against other diseases like type 2 diabetes, Alzheimer's disease, HIV etc. Ruthenium coordination and organometallic chemistry have seen tremendous expansion and assessment in recent years. The primary focus in the analytical measurement of ruthenium and potential as bioactive agents in medicine of the coordination complexes of ruthenium with various ligands, stems from its unique properties and its status as a valuable platinum group metal. The formation of Ruthenium-based complexes and their extensive applications in the fields like biology, nanoscience, medicine, photoactive materials, production of solar cells, catalysis, incorporation into platinum and palladium alloys have been the subject of numerous publications in recent years. Ruthenium's special capacity to exist in several oxidation states may be connected to these developments. For these reasons, a wide array of analytical methods for the metal’s determination have been successfully developed. Amongst all, UV/VIS spectrophotometric methods of determination, due to their simplicity, cost effectiveness, rapid analysis procedures and versatility, are put together in the present article. The review also examines the ruthenium complexes with potential medicinal applications.
Keywords: Ruthenium; Coordination compounds; Antitumor drugs; Spectrophotometric